Complete Instruction and Project Book for Contracting. A Library Cooperation Tool - Radcliffe, Walter H.; Kemper, Robert E.; Nebraska Library Commission, Lincoln ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
An important tool for establishing efficient total library service is contracting, which allows a unit of government or a library to obtain the use of the resources of another library according to its specific needs. A contract can cover services to be purchased, financial arrangements, administrative responsibilities, legal considerations, and the terms of the agreement. This handbook discusses the statutory basis for contracting by libraries, the forms of agreements, specific recommendations concerning contracts, and suggestions to be followed in developing contracts. As illustration, nine project suggestions are provided, with workable standard contracts. (Author/SL)
Availability: Nebraska Library Commission, State Capitol, Lincoln, Nebraska 68509.
ERIC Note: Library "Know Series" No. 3.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Contracts; Legal Responsibility; Library Cooperation; Library Expenditures; Library Services; Models; Library Funding -- Nebraska